Design of market liberalizing degree based on the evolutionary game bidding of generators. (April 2021) - Tang, Jiajun; Liu, Xinyi; He, Chuan; Li, Yating; Zhang, Zhi; Li, Jing; Lin, Zhemin; Li, Yongbo; Qian, Hanhan; Lin, Zhenzhi; Yang, Li
Abstract: The orderly release of electricity plan is an important measure for China's electricity market reform which also lead to excessive pressure for coal power units caused by the low planned electricity quantity. Allowing high-priced units to participate in the market can effectively alleviate the market pressure. However, the participation of high-priced units in electricity market will have an impact on the declaration behavior of other generators. In this context, an evolutionary game model of bidding for two groups of generators considering the market liberalizing degree (MLD) is proposed. Above all, the profit model of two kinds of generators is proposed under two bidding strategies considering the MLD. On this basis, an evolutionary game model of generators' bidding is built to qualitatively analyze the market equilibrium solution which is affected by the MLD coefficient. Thus, the expected evolutionary stable equilibrium of bidding can be formed spontaneously in electricity market by adjusting the MLD coefficient. The case studies are performed for demonstrating the proposed evolutionary game model of generators' bidding, and simulation results show that different MLD and the initial state of bidding behavior of generators will influence the final evolutionary stable equilibrium of bidding market, and it also shown that the government can make the electricity market develop towards​ the expected state by adjusting MLD and supervising the bidding behavior of generators.